Impact of pemetrexed on intracranial disease control and radiation necrosis in patients with brain metastases from non-small cell lung cancer receiving stereotactic radiation. Issue 3 (March 2018) - Cagney, Daniel N.; Martin, Allison M.; Catalano, Paul J.; Reitman, Zachary J.; Mezochow, Gabrielle A.; Lee, Eudocia Q.; Wen, Patrick Y.; Weiss, Stephanie E.; Brown, Paul D.; Ahluwalia, Manmeet S.; Arvold, Nils D.; Tanguturi, Shyam K.; et al.
Abstract: Background: Pemetrexed is a folate antimetabolite used in the management of advanced adenocarcinoma of the lung. We sought to assess the impact of pemetrexed on intracranial disease control and radiation-related toxicity among patients with adenocarcinoma of the lung who received stereotactic radiation for brain metastases. Materials/Methods: We identified 149 patients with adenocarcinoma of the lung and newly diagnosed brain metastases without a targetable mutation receiving stereotactic radiation. Kaplan–Meier plots and Cox regression were employed to assess whether use of pemetrexed was associated with intracranial disease control and radiation necrosis. Results: Among the entire cohort, 105 patients received pemetrexed while 44 did not. Among patients who were chemotherapy-naïve, use of pemetrexed ( n = 43) versus alternative regimens after stereotactic radiation ( n = 24) was associated with a reduced likelihood of developing new brain metastases (HR 0.42, 95% CI 0.22–0.79, p = 0.006) and a reduced need for salvage brain-directed radiation therapy (HR 0.36, 95% CI 0.18–0.73, p = 0.005). Pemetrexed use was associated with increased radiographic necrosis. (HR 2.70, 95% CI 1.09–6.70, p = 0.03). Conclusions: Patients receiving pemetrexed after brain-directed stereotactic radiation appear to benefit from improved intracranial disease control at the possible expense of radiation-related radiographic necrosis. Whether symptomatic radiation injury occurs more frequently in patients receiving pemetrexed requires further study.